Abaloparatide for risk reduction of nonvertebral and vertebral fractures in postmenopausal women with osteoporosis: a network meta-analysis - Reginster, J. -Y. (Osteoporos Int, 2019)
SUMMARY: This network meta-analysis assessed the efficacy of abaloparatide versus other treatment options to reduce the risk of fractures in women with postmenopausal osteoporosis. The analysis indicates that abaloparatide reduces the risk of fractures in women with postmenopausal osteoporosis versus placebo and compared with other treatment options. INTRODUCTION: This network meta-analysis (NMA) assessed the relative efficacy of abaloparatide versus other treatments to reduce the risk of fractures in women with postmenopausal osteoporosis (PMO). METHODS: PubMed®, Embase®, and the Cochrane Central Register of Controlled Trials were searched for randomized controlled trials published before December 20, 2017, that included women with PMO who were eligible to receive interventions for primary or secondary fracture prevention. The NMA was conducted by fracture site (vertebral [VF], nonvertebral [NVF], and wrist), with the relative risk (RR) of fracture versus placebo the main clinical endpoint. The NMA used fixed-effects and random-effects approaches. RESULTS: A total of 4978 articles were screened, of which 22 were included in the analysis. Compared with other treatments, abaloparatide demonstrated the greatest treatment effect relative to placebo in the VF network (RR = 0.13; 95% credible interval [CrI] 0.04–0.34), the NVF network (RR = 0.50; 95% CrI 0.28–0.85), and the wrist fracture network (RR = 0.39; CrI 0.15–0.90). Treatment ranking showed that abaloparatide had the highest estimated probability of preventing fractures in each of the networks (79% for VF, 70% for NVF, and 53% for wrist fracture) compared with other treatments. Individual networks demonstrated a good level of agreement with direct trial evidence and direct pair-wise comparisons. CONCLUSIONS: This NMA indicates that abaloparatide reduces the RR of VF, NVF, and wrist fracture in women with PMO with or without prior fracture versus placebo, compared with other treatment options. Limitations include that adverse events and drug costs were not considered, and that generalizability is limited to the trial populations and endpoints included in the NMA. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00198-019-04947-2) contains supplementary material, which is available to authorized users.